1997
DOI: 10.1021/jm9702894
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Photophysical Properties, in Vivo Photosensitizing Efficacy, and Human Serum Albumin Binding Properties of Some Novel Bacteriochlorins

Abstract: The synthesis, photophysical characteristics, in vivo photosensitizing efficacy, human serum albumin (HSA) binding properties, and skin phototoxicity of some stable bacteriochlorins were investigated. The novel bacteriochlorins, obtained from chlorophyll-a, have long-wavelength absorptions in the range lambda max = 734-758 nm. Preferential migration of ethyl over methyl substituents among ketobacteriochlorins obtained in the pinacol-pinacolone rearrangements of vic-dihydroxybacteriochlorins was confirmed by NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 32 publications
2
71
0
Order By: Relevance
“…It has been shown that DA and DP are two fluorescence probes, which are specific, respectively, for the two drug binding sites on HSA (Pandey et al 1997;Jisha et al 2006). In their free form, the two probes emit negligible fluorescence.…”
Section: Tryptophan Intrinsic Fluorescencementioning
confidence: 99%
“…It has been shown that DA and DP are two fluorescence probes, which are specific, respectively, for the two drug binding sites on HSA (Pandey et al 1997;Jisha et al 2006). In their free form, the two probes emit negligible fluorescence.…”
Section: Tryptophan Intrinsic Fluorescencementioning
confidence: 99%
“…Serum albumin is the major protein constituent of blood plasma. Specifi c delivery of ligands by BSA is considered to be due to the presence of two selective binding sites, namely site I and site II [55]. Dansyl amides are known to bind with site I through hydrophobic interactions [55].…”
Section: (B)mentioning
confidence: 99%
“…Specifi c delivery of ligands by BSA is considered to be due to the presence of two selective binding sites, namely site I and site II [55]. Dansyl amides are known to bind with site I through hydrophobic interactions [55]. We transferred the Au@SGAN/SGD superlattice film onto a quartz disc and dried it at room temperature.…”
Section: (B)mentioning
confidence: 99%
“…The donor to acceptor distance in both environments is less than 7 nm, indicating a static quenching interaction between the donor and acceptor according to Förster's nonradiative energy transfer theory. 48 To understand and confirm the site-selective binding of DASPMI with BSA, known site selective binding ligands, dansylamide (DNSA) for site I (subdomain IIA) and dansylproline (DP) for site II (subdomain IIIA) 50 were used. Initial addition of DNSA in the BSA-DASPMI complex showed a gradual decrease in fluorescence intensity and reached saturation at 0.7 mM (Figure 10a).…”
Section: Resultsmentioning
confidence: 99%